Resin particles
Resin particles with controlled alkali metal distribution and a layered structure of cationic and hydrophobic compounds address the challenge of maintaining storage properties in water-containing solutions, achieving enhanced biodegradability and storage performance.
Patent Information
- Application Number
- JP2021052445
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-25
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-03-25
AI Technical Summary
Resin particles with biodegradable resins face challenges in maintaining storage properties in water-containing solutions due to hydrolysis, which is often promoted by the presence of alkali metals on their surface.
The development of resin particles with a specific composition and surface treatment, where the alkali metal atomic weight ratio on the surface is controlled to satisfy 0≦(A/B)<0.15 and 0.005atomic%≦B≦0.5atomic%, and which include a first layer of cationic resin and a second layer of hydrophobic compounds, enhancing biodegradability and storage performance.
These resin particles exhibit improved biodegradability and storage properties in water-containing solutions, as the controlled alkali metal distribution reduces surface hydrolysis and the layered structure enhances biodegradation rates.
Smart Images

Figure 0007669753000001 
Figure 0007669753000002 
Figure 0007669753000003
Abstract
Description
[Technical field]
[0001] The present invention relates to resin particles. [Background technology]
[0002] Patent Document 1 proposes "a biodegradable resin composition comprising a poorly hydrolyzable biodegradable resin (A), an ester decomposition promoter (B) consisting of an easily hydrolyzable polymer, and an ester decomposition promoting auxiliary (C) consisting of inorganic particles that promote the hydrolysis of the ester decomposition promoter, the composition containing the ester decomposition promoter (B) in an amount of 0.01 to 30 parts by weight per 100 parts by weight of the biodegradable resin (A), and containing the ester decomposition promoting auxiliary (C) in an amount of 28 to 200 parts by weight per 100 parts by weight of the ester decomposition promoter (B)." Patent Document 2 proposes "a biodegradable resin composition comprising polylactic acid (A), polyglycolic acid (B), and calcium carbonate particles (C) as an ester decomposition-promoting assistant, wherein the content of the polyglycolic acid (B) is 1 to 10 parts by mass per 100 parts by mass of the polylactic acid (A), and the content of the calcium carbonate particles (C) is 30 to 100 parts by mass per 100 parts by mass of the polyglycolic acid (B)." Patent Document 3 proposes "a resin composition comprising a biodegradable polyester resin and a compound NaX(1) (wherein X represents a halogen atom) represented by general formula (1) as a crystal nucleating agent, wherein the compound represented by general formula (1) is dispersed in the polyester resin in the form of particles having an average particle size of 10 μm or less." [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5633291 [Patent Document 2] Patent No. 5829393 [Patent Document 3] JP 2009-249577 A Summary of the Invention [Problem to be solved by the invention]
[0004] The object of the present invention is to provide a resin particle having a base particle containing a biodegradable resin, in which the amount of alkali metal atoms A present on the surface of the resin particle relative to the total amount of atoms present on the surface of the resin particle measured by X-ray photoelectron spectroscopy and the amount of alkali metal atoms B present on the resin particle relative to the total amount of atoms present on the resin particle measured by X-ray fluorescent spectroscopy satisfy the relationship of (A / B)>0.15, 0.005 atomic%>B, or B>0.5 atomic%, or the amount of alkali metal atoms measured by X-ray photoelectron spectroscopy is greater than or equal to 0.005 atomic%. The alkali metal atomic weight [AL1] at the surface of the resin particle, the alkali metal atomic weight [AL2] at the surface after a 2 mm square area on the surface of the resin particle is etched for 5 minutes with an argon gas cluster ion gun having an output of 5 kV, and the alkali metal atomic weight [AL3] at the surface after a 2 mm square area on the surface of the resin particle is etched for 30 minutes with an argon gas cluster ion gun having an output of 5 kV satisfy [AL1] > [AL2] and [AL1] > [AL3], and thus resin particles can be obtained that are biodegradable and have excellent storage properties in solutions containing water. [Means for solving the problem]
[0005] The above problems are solved by the following means: <1> The composition has base particles containing a biodegradable resin, Resin particles in which the atomic weight A of an alkali metal present on the surface of a resin particle relative to the total atomic weight present on the surface of the resin particle, as measured by X-ray photoelectron spectroscopy, and the atomic weight B of an alkali metal present on the resin particle relative to the total atomic weight present on the resin particle, as measured by X-ray fluorescence spectroscopy, satisfy the relationship of 0≦(A / B)<0.15 and 0.005 atomic%≦B≦0.5 atomic%. <2> The alkali metal includes Na. <1> The resin particles according to claim 1. <3> The content of cellulose acylate is 50% by mass or more based on the total amount of the base particles. <1> or <2> The resin particles according to claim 1. <4> The cellulose acylate has at least two kinds of acyl groups. <3> The resin particles according to claim 1. <5> The cellulose acylate having at least two kinds of acyl groups is cellulose acetate butyrate. <4> The resin particles according to claim 1. <6> a first layer on the surface of the base particle, the first layer including at least one cationic resin selected from the group consisting of polyalkyleneimine, polyallylamine, and polyvinylamine; A second layer containing an anionic or nonionic hydrophobic compound, <1> ~ <5> 13. The resin particles according to any one of the above. <7> The amount of the coating with the first layer is 0.01% by mass or more and 20% by mass or less with respect to the entire base particle. <6> The resin particles according to claim 1. <8> The composition has base particles containing a biodegradable resin, Resin particles in which the alkali metal atomic weights measured by X-ray photoelectron spectroscopy satisfy the relationship [AL1] < [AL3] < [AL2], where the alkali metal atomic weight [AL1] at the surface of the resin particle, the alkali metal atomic weight [AL2] at the surface after a 2 mm square area of the resin particle surface is etched for 5 minutes with an argon gas cluster ion gun having an output of 5 kV, and the alkali metal atomic weight [AL3] at the surface after a 2 mm square area of the resin particle surface is etched for 30 minutes with an argon gas cluster ion gun having an output of 5 kV. Effect of the Invention
[0006] <1> According to the invention, there is provided a resin particle having a base particle containing a biodegradable resin, in which the amount of alkali metal atoms A present on the resin particle surface relative to the total amount of atoms present on the resin particle surface as measured by X-ray photoelectron spectroscopy, and the amount of alkali metal atoms B present on the resin particle relative to the total amount of atoms present on the resin particle as measured by X-ray fluorescence spectroscopy, satisfy the relationship (A / B)≧0.15, 0.005 atomic%>B, or B>0.5 atomic%, while having excellent storage properties in a solution containing water, compared to when the relationship is satisfied. <2> According to the present invention, there are provided resin particles which are biodegradable and have excellent storage properties in a solution containing water, as compared with a case in which the alkali metal contains an alkali metal element other than Na. <3> According to the present invention, there are provided resin particles which are biodegradable and have excellent storage properties in a solution containing water, as compared with particles in which the cellulose acylate content is less than 50 mass% relative to the entire base particles. <4> According to the present invention, there are provided resin particles which have excellent storage properties in a solution containing water while being biodegradable, as compared with a case where the cellulose acylate has one kind of acyl group. <5> According to the present invention, there are provided resin particles which are biodegradable and have excellent storage properties in a solution containing water, compared to cellulose acylate having at least two types of acyl groups other than cellulose acetate butyrate.
[0007] <6> According to the invention, there is provided a resin particle having base particles containing a biodegradable resin, in which the amount of alkali metal atoms A present on the resin particle surface relative to the total amount of atoms present on the resin particle surface, measured by X-ray photoelectron spectroscopy, and the amount of alkali metal atoms B present on the resin particle relative to the total amount of atoms present on the resin particle surface, measured by X-ray fluorescence spectroscopy, satisfy the relationship of 0≦(A / B)<0.15 and 0.005 atomic%≦B≦0.5 atomic%, wherein the resin particle has biodegradability and excellent storage stability in a solution containing water, compared to a resin particle that does not have a first layer containing at least one cationic resin, selected from polyalkyleneimine, polyallylamine, and polyvinylamine, and a second layer containing an anionic or nonionic hydrophobic compound, in that order, on the surface of the base particle. <7> According to the present invention, a first layer containing at least one cationic resin selected from the group consisting of polyalkyleneimine, polyallylamine, and polyvinylamine is formed on the surface of the base particle. In resin particles having, in this order, a first layer containing an anionic or nonionic hydrophobic compound, the amount of coating by the first layer is less than 0.01 mass % or more than 20 mass % of the entire base particle, and the resin particles have excellent storage properties in a solution containing water while being biodegradable. <8> According to the invention, there is provided a resin particle having a base particle containing a biodegradable resin, which has an alkali metal atomic weight measured by X-ray photoelectron spectroscopy, and which has excellent storage properties in a solution containing water while being biodegradable, compared to a case in which the alkali metal atomic weight [AL1] at the surface of the resin particle, the alkali metal atomic weight [AL2] at the surface after a 2 mm square area on the surface of the resin particle is etched for 5 minutes with an argon gas cluster ion gun having an output of 5 kV, and the alkali metal atomic weight [AL3] at the surface after a 2 mm square area on the surface of the resin particle is etched for 30 minutes with an argon gas cluster ion gun having an output of 5 kV satisfy [AL1]>[AL2] and [AL1]>[AL3]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described as an example. The description and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the present invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0009] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if the composition contains multiple substances corresponding to each component, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.
[0010] <Resin particles> The resin particles according to the first embodiment have base particles containing a biodegradable resin, and the atomic weight A of the alkali metal present on the resin particle surface relative to the total atomic weight present on the resin particle surface as measured by X-ray photoelectron spectroscopy (hereinafter also simply referred to as "atomic weight A") and the atomic weight B of the alkali metal present on the resin particle relative to the total atomic weight present on the resin particle as measured by X-ray fluorescence spectroscopy (hereinafter also simply referred to as "atomic weight B") satisfy the relationships 0≦(A / B)<0.15 and 0.005 atomic%≦B≦0.5 atomic%.
[0011] The resin particles according to the first embodiment have the above-mentioned constitution, and are biodegradable and have excellent storage properties in a solution containing water. The reason for this is presumed to be as follows.
[0012] Resin particles containing a biodegradable resin (hereinafter also referred to as biodegradable resin particles) may be contained in a solution containing water depending on the application. However, the biodegradable resin particles are easily hydrolyzed in a solution containing water. Therefore, the biodegradable resin particles have sometimes been insufficient in storage in a solution containing water. Although the reason is unclear, when an alkali metal is contained in a biodegradable resin particle, hydrolysis in a solution containing water tends to be promoted. And the storage property of the biodegradable resin particle in a solution containing water tends to depend on the ease of hydrolysis on the surface of the biodegradable resin particle. Therefore, when an alkali metal is contained on the surface of the biodegradable resin particle, the storage property of the biodegradable resin particle in a solution containing water is deteriorated.
[0013] In the resin particles according to the first embodiment, the atomic weight A and the atomic weight B satisfy the relationship of 0≦(A / B)<0.15 and 0.005 atomic%≦B≦0.5 atomic%. When the resin particles satisfy 0≦(A / B)<0.15, the amount of alkali metal present near the surface of the resin particles is reduced. Therefore, hydrolysis of the surface of the resin particles is less likely to occur. This improves storage stability in a solution containing water. On the other hand, when the resin particles satisfy the relationship 0.005 atomic%≦B≦0.5 atomic%, the resin particles contain an alkali metal inside. The alkali metal also tends to promote the biodegradability of the biodegradable resin, thereby ensuring the biodegradability of the resin particles.
[0014] From the above, it is presumed that the resin particles according to the first embodiment, due to the above-mentioned configuration, have excellent storage properties in a solution containing water while being biodegradable.
[0015] The resin particles of the second embodiment have base particles containing a biodegradable resin, and the alkali metal atomic weights measured by X-ray photoelectron spectroscopy satisfy the relationship [AL1]<[AL3]<[AL2] among the alkali metal atomic weight [AL2] on the surface of the resin particle after etching a 2 mm square area of the resin particle surface for 5 minutes with an argon gas cluster ion gun having an output of 5 kV, and the alkali metal atomic weight [AL3] on the surface of the resin particle after etching a 2 mm square area of the resin particle surface for 30 minutes with an argon gas cluster ion gun having an output of 5 kV.
[0016] The resin particles according to the second embodiment have the above-mentioned constitution, and are biodegradable and have excellent storage properties in a solution containing water. The reason for this is presumed to be as follows.
[0017] Here, [AL1] represents the amount of alkali metal atoms in the region near the surface of the resin particle, [AL2] represents the amount of alkali metal atoms in the region near 100 nm in the depth direction from the surface of the resin particle, and [AL3] represents the amount of alkali metal atoms in the region near the center of the resin particle. Therefore, by satisfying the relationship [AL1]<[AL3]<[AL2], the amount of alkali metal present near the surface of the resin particle is the smallest. This improves storage stability in a solution containing water. In addition, by making the amount of alkali metal atoms in the region near 100 nm in the depth direction from the surface of the resin particle the largest, biodegradation is promoted when it progresses to that region. Furthermore, by making the amount of alkali metal atoms in the region near the center of the resin particle the second largest, it becomes easier to ensure promoted biodegradation.
[0018] From the above, it is presumed that the resin particles according to the second embodiment, due to the above-mentioned configuration, have excellent storage properties in a solution containing water while being biodegradable.
[0019] Hereinafter, the resin particles corresponding to either the resin particles according to the first or second embodiment will be described in detail. However, an example of the resin particles of the present invention may be any one of the resin particles according to the first or second embodiment.
[0020] (base particle) -Biodegradable resin- The base particles include a biodegradable resin. Examples of the base particles include particles containing a biodegradable resin as a main component, and specifically, examples of the base particles include particles containing 90 mass %, 95 mass %, 98 mass %, or 100 mass % of biodegradable resin based on the entire base particle. Here, biodegradable resin is a resin that is decomposed into water and carbon dioxide by microorganisms. Specifically, biodegradable resin means a resin whose aerobic biodegradation rate measured according to a method conforming to ISO-14855-2 (2018) is 50% or more in one month.
[0021] Examples of the biodegradable resin include cellulose acylate, polyester, and natural polymers.
[0022] Cellulose acylate is a cellulose derivative in which at least a portion of the hydroxyl groups in cellulose are replaced with acyl groups (acylation). An acyl group is -CO-R AC (R AC represents a hydrogen atom or a hydrocarbon group.) Examples of cellulose acylate include cellulose derivatives represented by the following general formula (CA).
[0023] Examples of the polyester include aliphatic polyesters and aliphatic aromatic polyesters. Examples of aliphatic polyesters include polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxybutyrate, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), polycaprolactone, polybutylene succinate (PBS), polybutylene succinate / adipate (PBSA), and polyhydroxyalkanoates such as polyethylene succinate (PBA). Examples of the aliphatic aromatic polyester include polybutylene adipate / terephthalate copolymer resin (PBAH), polytetramethylene adipate / terephthalate copolymer resin, and the like.
[0024] Examples of natural polymers include starch, cellulose, chitin, chitosan, gluten, gelatin, zein, soy protein, collagen, and keratin.
[0025] From the viewpoint of improving biodegradability, the biodegradable resin is preferably cellulose acylate.
[0026] Cellulose acylate Cellulose acylate is, for example, a cellulose derivative represented by the following general formula (CA).
[0027] [ka]
[0028] In the general formula (CA), A1, A2, and A3 each independently represent a hydrogen atom or an acyl group, and n represents an integer of 2 or more. However, at least a part of the n A1s, n A2s, and n A3s represents an acyl group. The n A1s in a molecule may all be the same, some may be the same, or different from each other. Similarly, the n A2s and n A3s in a molecule may all be the same, some may be the same, or different from each other.
[0029] The acyl group represented by A1, A2, and A3 may have a hydrocarbon group that is linear, branched, or cyclic, but is preferably linear or branched, and more preferably linear.
[0030] The hydrocarbon group in the acyl group represented by A1, A2, and A3 may be a saturated hydrocarbon group or an unsaturated hydrocarbon group, but is more preferably a saturated hydrocarbon group.
[0031] The acyl group represented by A1, A2 and A3 is preferably an acyl group having a carbon number of 1 to 6. That is, the cellulose acylate is preferably an acyl group having a carbon number of 1 to 6.
[0032] The acyl group represented by A1, A2, and A3 may be a group in which a hydrogen atom in the acyl group is substituted with a halogen atom (e.g., a fluorine atom, a bromine atom, an iodine atom), an oxygen atom, a nitrogen atom, or the like, but is preferably unsubstituted.
[0033] Examples of the acyl group represented by A1, A2, and A3 include a formyl group, an acetyl group, a propionyl group, a butyryl group (butanoyl group), a propenoyl group, a hexanoyl group, etc. Among these, from the viewpoint of improving the biodegradation rate of the resin particles, the acyl group is more preferably an acyl group having 2 to 4 carbon atoms, and even more preferably an acyl group having 2 or 3 carbon atoms.
[0034] Examples of the cellulose acylate include cellulose acetate (cellulose monoacetate, cellulose diacetate (DAC), cellulose triacetate), cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB).
[0035] From the viewpoint of improving the biodegradation rate of the resin particles, the cellulose acylate preferably has two or more kinds of acyl groups. Specifically, from the viewpoint of improving the biodegradation rate of the resin particles, the cellulose acylate is preferably cellulose acetate, cellulose acetate propionate (CAP), or cellulose acetate butyrate (CAB), more preferably cellulose acetate propionate (CAP), and even more preferably cellulose acetate butyrate (CAB).
[0036] Cellulose acylate having two or more kinds of acyl groups tends to have a high biodegradation rate, and therefore, by using cellulose acylate having two or more kinds of acyl groups, even resin particles having a small amount of alkali metal on the particle surface can more easily maintain biodegradability. Cellulose acetate butyrate tends to have a particularly high rate of biodegradability, and so by using cellulose acetate butyrate, biodegradability is more likely to be improved.
[0037] The cellulose acylate may be used alone or in combination of two or more kinds.
[0038] The weight average degree of polymerization of the cellulose acylate is preferably 200 or more and 1,000 or less, more preferably 500 or more and 1,000 or less, and even more preferably 600 or more and 1,000 or less.
[0039] The weight-average degree of polymerization of cellulose acylate is determined from the weight-average molecular weight (Mw) by the following procedure. First, the weight average molecular weight (Mw) of the cellulose acylate is measured in terms of polystyrene using tetrahydrofuran with a gel permeation chromatography apparatus (GPC apparatus: Tosoh Corporation, HLC-8320GPC, column: TSKgel α-M). Then, the degree of polymerization of cellulose acylate is calculated by dividing the molecular weight of the constituent unit of cellulose acylate. For example, when the substituent of cellulose acylate is an acetyl group, the molecular weight of the constituent unit is 263 when the degree of substitution is 2.4, and 284 when the degree of substitution is 2.9.
[0040] From the viewpoint of improving the biodegradation rate of the resin particles, the substitution degree of the cellulose acylate is preferably from 2.1 to 2.9, more preferably from 2.2 to 2.9, further preferably from 2.3 to 2.9, and particularly preferably from 2.6 to 2.9.
[0041] In cellulose acetate propionate (CAP), the ratio of the substitution degree of acetyl groups to propionyl groups (acetyl groups / propionyl groups) is preferably 0.01 or more and 1 or less, more preferably 0.05 or more and 0.1 or less, from the viewpoint of improving the biodegradation rate of the resin particles.
[0042] In cellulose acetate butyrate (CAB), the ratio of the substitution degree of acetyl groups to butyryl groups (acetyl groups / butyryl groups) is preferably 0.05 to 3.5, more preferably 0.5 to 3.0, from the viewpoint of improving the biodegradation rate of the resin particles.
[0043] The degree of substitution of cellulose acylate is an index showing the degree to which hydroxyl groups of cellulose are substituted with acyl groups. In other words, the degree of substitution is an index showing the degree of acylation of cellulose acylate. Specifically, the degree of substitution means the intramolecular average number of substitutions in which three hydroxyl groups in a D-glucopyranose unit of cellulose acylate are substituted with acyl groups. The degree of substitution is determined from the integral ratio of the peaks of hydrogen derived from cellulose and hydrogen derived from acyl groups by 1H-NMR (JMN-ECA / JEOL RESONANCE).
[0044] These biodegradable resins may be used alone or in combination of two or more kinds.
[0045] The content of cellulose acylate is preferably 50% by mass or more based on the total amount of the base particles. Cellulose acylate tends to have a high biodegradation rate. Therefore, by setting the content of cellulose acylate within the above range, even resin particles with a small amount of alkali metal on the particle surface are more likely to maintain biodegradability.
[0046] -Plasticizer- The base particles may contain a plasticizer. Examples of the plasticizer include ester compounds, cardanol compounds, camphor, metal soaps, polyols, and polyalkylene oxides. From the viewpoint of improving the mechanical properties of the resin particles, the plasticizer is preferably at least one of ester compounds and cardanol compounds. The plasticizer may be used alone or in combination of two or more.
[0047] Examples of the ester compound include fatty acid esters (adipic acid esters, citrate esters, sebacic acid esters, azelaic acid esters, phthalic acid esters, and acetate esters), phosphate esters, condensed phosphate esters, glycol esters (e.g., benzoic acid glycol esters), and modified fatty acid esters (e.g., epoxidized fatty acid esters). Examples of the esters include monoesters, diesters, triesters, and polyesters. Among these, dicarboxylates (adipic acid diesters, sebacic acid diesters, azelaic acid diesters, and phthalic acid diesters) are preferred.
[0048] The plasticizer is preferably an adipic acid ester, which has high affinity with cellulose acylate and disperses almost uniformly in the cellulose acylate, thereby improving the thermal fluidity more than other plasticizers.
[0049] The adipic acid ester may be a mixture of an adipic acid ester and other components. Commercially available products of such mixtures include Daifatty 101 manufactured by Daihachi Chemical Industry Co., Ltd.
[0050] Examples of fatty acid esters such as citrate esters, sebacic acid esters, azelaic acid esters, phthalic acid esters, and acetate esters include esters of fatty acids and alcohols. Examples of the alcohols include monohydric alcohols such as methanol, ethanol, propanol, butanol, and 2-ethylhexanol; and polyhydric alcohols such as glycerin, polyglycerin (diglycerin, etc.), pentaerythritol, ethylene glycol, diethylene glycol, propylene glycol, butylene glycol, trimethylolpropane, trimethylolethane, and sugar alcohols.
[0051] Examples of the glycol in the glycol benzoate include ethylene glycol, diethylene glycol, and propylene glycol.
[0052] Epoxidized fatty acid esters are ester compounds having a structure in which the carbon-carbon unsaturated bonds of unsaturated fatty acid esters have been epoxidized (i.e., oxacyclopropane). Examples of epoxidized fatty acid esters include esters of alcohols and fatty acids in which some or all of the carbon-carbon unsaturated bonds in unsaturated fatty acids (e.g., oleic acid, palmitoleic acid, vaccenic acid, linoleic acid, linolenic acid, nervonic acid, etc.) have been epoxidized. Examples of the alcohols include monohydric alcohols such as methanol, ethanol, propanol, butanol, and 2-ethylhexanol; polyhydric alcohols such as glycerin, polyglycerin (diglycerin, etc.), pentaerythritol, ethylene glycol, diethylene glycol, propylene glycol, butylene glycol, trimethylolpropane, trimethylolethane, and sugar alcohols; and the like.
[0053] The molecular weight (or weight average molecular weight) of the ester compound as a plasticizer is preferably from 200 to 2000, more preferably from 250 to 1500, and even more preferably from 280 to 1000. The weight average molecular weight of the ester compound is a value measured in accordance with the method for measuring the weight average molecular weight of cellulose acylate, unless otherwise specified.
[0054] It is also preferable to use a cardanol compound as the plasticizer. The cardanol compound refers to a component contained in a naturally derived compound made from cashew (for example, a compound represented by the following structural formulas (b-1) to (b-4)) or a derivative of the above component.
[0055] [ka]
[0056] The cardanol compound may be a mixture of naturally occurring compounds made from cashews (hereinafter also referred to as a "cashew-derived mixture").
[0057] The cardanol compound may be a derivative from a mixture derived from cashew. Examples of the derivative from a mixture derived from cashew include the following mixtures and simple substances.
[0058] A mixture in which the composition ratio of each component in the cashew-derived mixture has been adjusted A single substance isolated from a mixture of cashew-derived ingredients -Mixtures containing modified components of cashew-derived mixtures - Mixtures containing polymers obtained by polymerizing ingredients in cashew-derived mixtures Mixtures containing modified polymers obtained by modifying and polymerizing components in a cashew-derived mixture A mixture containing a modified product obtained by further modifying the components in the mixture with the adjusted composition ratio. A mixture containing a polymer obtained by further polymerizing the components in the mixture with the adjusted composition ratio. A mixture containing a modified polymer obtained by further modifying and polymerizing the components in the mixture whose composition ratio has been adjusted. A denatured product obtained by further denaturing the isolated monomer A polymer obtained by further polymerizing the isolated monomer. A modified polymer obtained by further modifying and polymerizing the isolated monomer. Here, the monomer also includes polymers such as dimers and trimers.
[0059] From the viewpoint of improving the biodegradation rate of the resin particles, the cardanol compound is preferably at least one compound selected from the group consisting of compounds represented by general formula (CDN1) and polymers of compounds represented by general formula (CDN1).
[0060] [ka]
[0061] In the general formula (CDN1), R 1 R represents an alkyl group which may have a substituent, or an unsaturated aliphatic group which has a double bond and which may have a substituent. 2represents a hydroxy group, a carboxy group, an alkyl group which may have a substituent, or an unsaturated aliphatic group which has a double bond and may have a substituent. P2 represents an integer of 0 to 4. When P2 is 2 or more, a plurality of R 2 may be the same group or different groups.
[0062] In the general formula (CDN1), R 1 The alkyl group which may have a substituent, represented by the formula (I), is preferably an alkyl group having 3 to 30 carbon atoms, more preferably an alkyl group having 5 to 25 carbon atoms, and further preferably an alkyl group having 8 to 20 carbon atoms. Examples of the substituent include a hydroxy group; a substituent containing an ether bond, such as an epoxy group or a methoxy group; and a substituent containing an ester bond, such as an acetyl group or a propionyl group. Examples of the alkyl group which may have a substituent include a pentadecane-1-yl group, a heptan-1-yl group, an octan-1-yl group, a nonan-1-yl group, a decan-1-yl group, an undecane-1-yl group, a dodecane-1-yl group, and a tetradecane-1-yl group.
[0063] In the general formula (CDN1), R 1 The unsaturated aliphatic group having a double bond and optionally having a substituent, represented by the formula (I) is preferably an unsaturated aliphatic group having 3 to 30 carbon atoms, more preferably an unsaturated aliphatic group having 5 to 25 carbon atoms, and even more preferably an unsaturated aliphatic group having 8 to 20 carbon atoms. The unsaturated aliphatic group preferably has 1 or more and 3 or less double bonds. Examples of the substituent include those exemplified as the substituent for the alkyl group. Examples of the unsaturated aliphatic group having a double bond and optionally having a substituent include a pentadec-8-en-1-yl group, a pentadeca-8,11-dien-1-yl group, a pentadeca-8,11,14-trien-1-yl group, a pentadec-7-en-1-yl group, a pentadeca-7,10-dien-1-yl group, and a pentadeca-7,10,14-trien-1-yl group.
[0064] In the general formula (CDN1), R 1 As the alkyl group, a pentadec-8-en-1-yl group, a pentadeca-8,11-dien-1-yl group, a pentadeca-8,11,14-trien-1-yl group, a pentadec-7-en-1-yl group, a pentadeca-7,10-dien-1-yl group, and a pentadeca-7,10,14-trien-1-yl group are preferable.
[0065] In the general formula (CDN1), R 2 The alkyl group which may have a substituent and the unsaturated aliphatic group which has a double bond and may have a substituent represented by R 1 Similarly, preferred examples include those exemplified as the alkyl group which may have a substituent and the unsaturated aliphatic group which has a double bond and may have a substituent, represented by the formula (I) below.
[0066] The compound represented by the general formula (CDN1) may be further modified, for example, epoxidized, and from the viewpoint of improving the biodegradation rate of the resin particles, specifically, it is preferable that the compound represented by the general formula (CDN1) has a structure in which the hydroxyl group is replaced by the following group (EP), that is, the compound represented by the following general formula (CDN1-e).
[0067] [ka]
[0068] In the group (EP) and the general formula (CDN1-e), L EP represents a single bond or a divalent linking group.1 , R 2 and P2 are R in general formula (CDN1), 1 , R 2 and P2.
[0069] In the group (EP) and the general formula (CDN1-e), L EP Examples of the divalent linking group represented by the formula (I) include an alkylene group which may have a substituent (preferably an alkylene group having 1 to 4 carbon atoms, more preferably an alkylene group having 1 carbon atom), -CH 2 CH 2 OCH 2 CH 2 - group and the like. The above-mentioned substituents include R 1 The substituents are the same as those listed in the above.
[0070] L EP As the alkyl group, a methylene group is preferable.
[0071] The polymer of the compound represented by the general formula (CDN1) refers to a polymer of at least two or more compounds represented by the general formula (CDN1) polymerized with or without a linking group.
[0072] An example of a polymer obtained by polymerizing the compound represented by general formula (CDN1) is a compound represented by the following general formula (CDN2).
[0073] [ka]
[0074] In the general formula (CDN2), R 11 , R 12 and R 13 R each independently represents an alkyl group which may have a substituent, or an unsaturated aliphatic group which has a double bond and which may have a substituent. 21 , R 22 and R 23Each independently represents a hydroxy group, a carboxy group, an alkyl group which may have a substituent, or an unsaturated aliphatic group which has a double bond and may have a substituent. P21 and P23 each independently represent an integer of 0 or more and 3 or less, and P22 represents an integer of 0 or more and 2 or less. L 1 and L 2 Each independently represents a divalent linking group. n represents an integer of 0 to 10. When P21 is 2 or more, a plurality of R 21 , when P22 is 2 or more, there are multiple R 22 , and when P23 is 2 or more, there are multiple R 23 may be the same or different groups. When n is 2 or more, a plurality of R 12 , R 22 and L 1 may be the same or different groups, and when n is 2 or greater, a plurality of P22s may be the same or different in number.
[0075] In the general formula (CDN2), R 11 , R 12 , R 13 , R 21 , R 22 and R 23 The alkyl group which may have a substituent and the unsaturated aliphatic group which has a double bond and may have a substituent represented by R 1 The above-listed examples are also preferred.
[0076] In the general formula (CDN2), L 1 and L 2 Examples of the divalent linking group represented by include an alkylene group which may have a substituent (preferably an alkylene group having 2 to 30 carbon atoms, more preferably an alkylene group having 5 to 20 carbon atoms). The above-mentioned substituents include R 1 The substituents are the same as those listed in the above.
[0077] In formula (CDN2), n is preferably 1 or more and 10 or less, and more preferably 1 or more and 5 or less.
[0078] The compound represented by the general formula (CDN2) may be further modified, for example, may be epoxidized, specifically, may be a compound having a structure in which the hydroxy group of the compound represented by the general formula (CDN2) is replaced with a group (EP), that is, may be a compound represented by the following general formula (CDN2-e).
[0079] [ka]
[0080] In the general formula (CDN2-e), R 11 , R 12 , R 13 , R 21 , R 22 , R 23 , P21, P22, P23, L 1 , L 2 and n are each R in general formula (CDN2). 11 , R 12 , R 13 , R 21 , R 22 , R 23 , P21, P22, P23, L 1 , L 2 and n. In the general formula (CDN2-e), L EP1 , L EP2 and L EP3 Each of L independently represents a single bond or a divalent linking group. EP2 may be the same group or different groups.
[0081] In the general formula (CDN2-e), L EP1 , L EP2 and L EP3 The divalent linking group represented by is L in the general formula (CDN1-e). EPSimilarly, the divalent linking group represented by the formula (I) is preferably the same as the divalent linking group represented by the formula (I).
[0082] The polymer obtained by polymerizing the compound represented by the general formula (CDN1) may be, for example, a polymer obtained by three-dimensionally crosslinking polymerizing at least three or more compounds represented by the general formula (CDN1) with or without a linking group. Examples of the polymer obtained by three-dimensionally crosslinking polymerizing the compound represented by the general formula (CDN1) include compounds represented by the following structural formulas.
[0083] [ka]
[0084] In the above structural formula, R 10 , R 20 and P20 are R in general formula (CDN1), 1 , R 2 and P2. 10 represents a single bond or a divalent linking group. 10 , R 20 and L 10 may be the same or different groups. 20 may be the same or different numbers.
[0085] In the above structural formula, L 10 Examples of the divalent linking group represented by include an alkylene group which may have a substituent (preferably an alkylene group having 2 to 30 carbon atoms, more preferably an alkylene group having 5 to 20 carbon atoms). The above-mentioned substituents include R 1 The substituents are the same as those listed in the above.
[0086] The compound represented by the above structural formula may be further modified, for example, may be epoxidized.Specifically, the compound represented by the above structural formula may have a structure in which the hydroxyl group is replaced with a group (EP), and for example, the compound represented by the following structural formula, that is, the polymer in which the compound represented by general formula (CDN1-e) is three-dimensionally crosslinked and polymerized, may be mentioned.
[0087] [ka]
[0088] In the above structural formula, R 10 , R 20 and P20 are R in the general formula (CDN1-e), 1 , R 2 and P2. 10 represents a single bond or a divalent linking group. 10 , R 20 and L 10 may be the same or different groups. 20 may be the same or different numbers.
[0089] In the above structural formula, L 10 Examples of the divalent linking group represented by include an alkylene group which may have a substituent (preferably an alkylene group having 2 to 30 carbon atoms, more preferably an alkylene group having 5 to 20 carbon atoms). The above-mentioned substituents include R 1 The substituents are the same as those listed in the above.
[0090] From the viewpoint of improving the transparency of the resin molded body, the cardanol compound preferably contains a cardanol compound having an epoxy group, and is more preferably a cardanol compound having an epoxy group.
[0091] Commercially available cardanol compounds may be used. Commercially available products include, for example, Cardolite's NX-2024, Ultra LITE 2023, NX-2026, GX-2503, NC-510, LITE 2020, NX-9001, NX-9004, NX-9007, NX-9008, NX-9201, and NX-9203, and Tohoku Kako's LB-7000, LB-7250, and CD-5L. Commercially available cardanol compounds having an epoxy group include, for example, Cardolite's NC-513, NC-514S, NC-547, LITE513E, and Ultra LTE 513.
[0092] From the viewpoint of improving the biodegradation rate of the resin molded article, the hydroxyl value of the cardanol compound is preferably 100 mgKOH / g or more, more preferably 120 mgKOH / g or more, and even more preferably 150 mgKOH / g or more. The hydroxyl value of the cardanol compound is measured according to ISO14900 Method A.
[0093] When a cardanol compound having an epoxy group is used as the cardanol compound, from the viewpoint of improving the transparency of a resin molded product, the epoxy equivalent is preferably from 300 to 500, more preferably from 350 to 480, and even more preferably from 400 to 470. The epoxy equivalent of the cardanol compound having an epoxy group is measured in accordance with ISO3001.
[0094] The molecular weight of the cardanol compound is preferably 250 or more and 1,000 or less, more preferably 280 or more and 800 or less, and even more preferably 300 or more and 500 or less, from the viewpoint of improving the biodegradation rate of the resin molded article.
[0095] The cardanol compound may be used alone or in combination of two or more kinds.
[0096] The content of the plasticizer is preferably from 0 to 50% by mass, more preferably from 5 to 40% by mass, and even more preferably from 10 to 30% by mass, based on the total mass of the resin particles.
[0097] -Other ingredients- The base particles may contain other components. Examples of other components include plasticizers, flame retardants, compatibilizers, release agents, light resistance agents, weather resistance agents, colorants, pigments, modifiers, anti-drip agents, antistatic agents, hydrolysis inhibitors, fillers, reinforcing agents (glass fibers, carbon fibers, talc, clay, mica, glass flakes, milled glass, glass beads, crystalline silica, alumina, silicon nitride, aluminum nitride, boron nitride, etc.), acid acceptors for preventing release of acetic acid (oxides such as magnesium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, and hydrotalcite; calcium carbonate; talc; etc.), and reactive trapping agents (for example, epoxy compounds, acid anhydride compounds, carbodiimides, etc.). The content of each of the other components is preferably 0% by mass or more and 5% by mass or less based on the total amount of the base particles, where "0% by mass" means that no other components are included.
[0098] The base particles may contain other resins besides the biodegradable resin. However, when other resins are contained, the content of the other resins relative to the entire base particles is preferably 5% by mass or less, and preferably less than 1% by mass. It is more preferable that the base particles do not contain other resins (i.e., 0% by mass). Examples of other resins include conventionally known thermoplastic resins, specifically, polycarbonate resins; polypropylene resins; polyester resins; polyolefin resins; polyester carbonate resins; polyphenylene ether resins; polyphenylene sulfide resins; polysulfone resins; polyether sulfone resins; polyarylene resins; polyetherimide resins; polyacetal resins; polyvinyl acetal resins; polyketone resins; polyether ketone resins; polyether ether ketone resins; polyaryl ketone resins; polyether nitrile resins; liquid crystal resins; polybenzimidazole resins; polypa Examples of the resin include lavane acid resins, vinyl polymers or copolymers obtained by polymerizing or copolymerizing one or more vinyl monomers selected from the group consisting of aromatic alkenyl compounds, methacrylic acid esters, acrylic acid esters, and vinyl cyanide compounds, diene-aromatic alkenyl compound copolymers, vinyl cyanide-diene-aromatic alkenyl compound copolymers, aromatic alkenyl compound-diene-vinyl cyanide-N-phenylmaleimide copolymers, vinyl cyanide-(ethylene-diene-propylene (EPDM))-aromatic alkenyl compound copolymers, vinyl chloride resins, chlorinated vinyl chloride resins, etc. These resins may be used alone or in combination of two or more.
[0099] (First and second layers) The resin particles according to this embodiment preferably have, on the surface of the base particle, a first layer containing at least one cationic resin selected from the group consisting of polyalkyleneimine, polyallylamine, and polyvinylamine, and a second layer containing an anionic or nonionic hydrophobic compound, in this order. By having the first layer and the second layer, the alkali metal atomic weight A on the surface of the resin particle is more likely to be reduced, and therefore the storage property in a solution containing water is more improved.
[0100] -First layer- The first layer is a resin layer present on the surface of the base particle, and contains at least one cationic resin selected from the group consisting of polyalkyleneimine, polyallylamine, and polyvinylamine.
[0101] The cationic resin may be any of polyalkyleneimine, polyallylamine and polyvinylamine, but from the viewpoints of increasing the rate of biodegradation over time and decreasing the initial rate of biodegradation, polyalkyleneimine is preferred.
[0102] As the polyalkyleneimine, from the viewpoint of improving the biodegradation rate over time and decreasing the initial biodegradation rate, a polyalkyleneimine having a structural unit with an alkylene group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms, more preferably 1 to 2 carbon atoms), is preferred, and polyethyleneimine is more preferred.
[0103] In particular, polyethyleneimine is a compound with high adhesion and high water absorption. This is because the amino group of polyethyleneimine forms a hydrogen bond with a hydroxyl group, an ionic bond with a carboxyl group, and a covalent bond with a carbonyl group. Since polyethyleneimine has a polar group (amino group) and a hydrophobic group (ethylene group) in its structure, it has the property of easily bonding different substances. In addition, polyethyleneimine is a compound having high cationicity, and therefore, polyethyleneimine exists as a polycation in water and neutralizes and adsorbs anionic substances. In addition, polyethyleneimine is a highly reactive compound because it has a highly reactive primary amino group or secondary amino group, and therefore it reacts easily with various compounds. Therefore, when polyethyleneimine is used as the polyalkyleneimine, the base particles are more firmly coated with the second layer containing the hydrophobic compound, and while the base particles have a biodegradation rate over time, the initial biodegradation rate tends to be slower.
[0104] The number average molecular weight of the cationic resin is preferably 300 to 100,000, more preferably 10,000 to 85,000, and even more preferably 50,000 to 80,000, from the viewpoints of improving the biodegradation rate over time and preventing a decrease in the initial biodegradation rate. The number average molecular weight of the cationic resin is measured in polystyrene equivalent terms using tetrahydrofuran with a gel permeation chromatography apparatus (GPC apparatus: HLC-8320GPC, manufactured by Tosoh Corporation, column: TSKgel α-M).
[0105] -Second layer- The second layer is a compound layer disposed on the first layer, and includes an anionic or nonionic compound or a hydrophobic compound.
[0106] Examples of anionic or nonionic compounds or hydrophobic compounds include hydrophobic compounds having an anionic group (such as -COOH (carboxyl group), -SOH (sulfonic group)) and hydrophobic compounds having no cationic or anionic groups. The hydrophobic compound refers to a compound that imparts hydrophobicity (specifically, water contact angle) to the biodegradable resin particles described below.
[0107] Examples of the hydrophobic compound include a silicone compound, a hydrocarbon compound, a fatty acid compound, an acrylic resin, a polyester resin, and a urethane resin. Among these, from the viewpoints of improving the biodegradation rate over time and decreasing the initial biodegradation rate, at least one selected from the group consisting of silicone compounds, hydrocarbon compounds, fatty acid compounds, acrylic resins, polyester resins, and urethane resins is preferred.
[0108] Examples of silicone compounds include dimethylpolysiloxane, methylpolysiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentanesiloxane, methylcyclopolysiloxane, various modified silicone oils (alkyl-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, fluorine-modified silicone oil, amino-modified silicone oil, etc.), MQ resin, silicone rubber, etc. Among these, from the viewpoints of improving the biodegradation rate over time and decreasing the initial biodegradation rate, the silicone compound is preferably at least one selected from the group consisting of dimethylpolysiloxane, methylpolysiloxane, MQ resin, and silicone rubber. Here, MQ resin refers to a silicone resin having M units, which are monofunctional siloxane units [(CH3)3SiO1 / 2], and Q units, which are tetrafunctional siloxane units [SiO4 / 2].
[0109] Commercially available silicone compounds include silicone compounds manufactured by Shin-Etsu Chemical Co., Ltd. (KM-902, KM-903, KM-910, KM-9729, POLON-MN-ST, KM-9737A, KM-9782, KM-9738A, KM-752T, POLON-MF-33, KM-9717, X-51-1302M (MQ resin), POLON-MF-56, KM-2002-L-1, KM-2002-T, KM-9772, KM-9749, POLON-MF-40, KM-9729, X-52-1133, etc.), and silicone compounds manufactured by Asahi Kasei Wacker Silicone Co., Ltd. (BELSIL DM3112VP).
[0110] Examples of the hydrocarbon compounds include petroleum waxes (paraffin wax, microcrystalline wax, petrolatum wax, etc.) and synthetic hydrocarbon waxes (polyethylene wax, polypropylene wax, polybutene wax, Fischer-Tropsch wax, etc.). Among these, from the viewpoint of improving the biodegradation rate over time and decreasing the initial biodegradation rate, the hydrocarbon compound is preferably at least one selected from the group consisting of paraffin wax, microcrystalline wax, polyethylene wax, and polypropylene wax.
[0111] Commercially available hydrocarbon compounds include microcrystalline wax (EMUSTAR-0001, etc.) manufactured by Nippon Seiro Co., Ltd., paraffin wax (EMUSTAR-0135, etc.) manufactured by Nippon Seiro Co., Ltd., paraffin wax (AQUACER 497, etc.) manufactured by BYK Co., Ltd., polyethylene wax (AQUACER 507, AQUACER 840, AQUACER 1547, AQUACER 272, etc.) manufactured by BYK Co., Ltd., polyethylene wax (Hi-Tech E-2213, Hi-Tech E-6324, etc.) manufactured by Toho Chemical Co., Ltd., polypropylene wax (AQUACER 593, etc.) manufactured by BYK Co., Ltd., and polypropylene (Hi-Tech P-9018, Hi-Tech P-5060P, etc.) manufactured by Toho Chemical Co., Ltd.
[0112] Examples of fatty acid compounds include vegetable oils containing fatty acids (castor oil, tung oil, linseed oil, shortening, corn oil, soybean oil, sesame oil, rapeseed oil, sunflower oil, rice oil, camellia oil, coconut oil, palm oil, walnut oil, olive oil, peanut oil, almond oil, jojoba oil, cocoa butter, shea butter, neem oil, safflower oil, Japan wax, candelilla wax, rice wax, carnauba wax, etc.). Among these, from the viewpoints of improving the biodegradation rate over time and decreasing the initial biodegradation rate, at least one wax selected from the group consisting of carnauba wax, rice wax, candelilla wax, palm wax, castor oil wax, soybean oil wax, and sunflower oil wax is preferred.
[0113] Commercially available fatty acid compounds include carnauba wax (EMUSTAR-0413 (carnauba wax)) manufactured by Nippon Seiro Co., Ltd., rice wax (AQUASPROUT-7300, etc.) manufactured by Nippon Seiro Co., Ltd., palm wax (AQUASPROUT-7100, etc.) manufactured by Nippon Seiro Co., Ltd., castor oil wax (AQUASPROUT-7500, etc.) manufactured by Nippon Seiro Co., Ltd., soybean oil wax (AQUASPROUT-7200, etc.) manufactured by Nippon Seiro Co., Ltd., sunflower oil wax (AQUASPROUT-7400, etc.) manufactured by Nippon Seiro Co., Ltd., palm oil wax (Cuckoo Ace TKE, etc.) manufactured by Nippon Seiro Co., Ltd., and the like.
[0114] Examples of the acrylic resin include well-known acrylic resins such as polymers of acrylic acid and polymers of alkyl acrylates. Examples of commercially available acrylic resins include acrylic resins manufactured by Taisei Fine Co., Ltd. (3WX-2015, 3MF-320, 3MF-333, 3MF-407, etc.) and acrylic resins manufactured by DIC Corporation (COAT SFC-6440, BONCOAT CE-6270, BONCOAT CE-6400, BONCOAT CF-2800, etc.).
[0115] Examples of the polyester resin include well-known polyester resins such as polycondensates of polyvalent carboxylic acids and polyhydric alcohols, and ring-opening polycondensates of cyclic lactams. Commercially available polyester resins include, for example, polyester resins manufactured by Takamatsu Oil Co., Ltd. (A-110F, A-160P, A-520, A-613D, A-615GE, A-640, A-645GH, A-647GEX, etc.).
[0116] Examples of the urethane resin include well-known urethane resins such as polyester-based polyurethane, polyether-based polyurethane, polycarbonate-based polyurethane, etc. Furthermore, as the urethane resin, a material having a urethane polymer shell layer around an acrylic polymer core may be used. Commercially available urethane resins include, for example, urethane resins manufactured by Taisei Fine Co., Ltd. (WEM-031U, WEM-200U, WEM-321U, WEM-3000, WBR-016U, WBR-2101, etc.).
[0117] -Content of each layer- In the biodegradable resin particles according to this embodiment, from the viewpoint of improving the biodegradation rate over time and decreasing the initial biodegradation rate, the mass ratio of the coating amount of the cationic resin in the first layer to the coating amount of the hydrophobic compound in the second layer (coating amount of cationic resin / coating amount of hydrophobic compound) is preferably 0.05 or more and 20 or less, more preferably 0.1 or more and 10 or less, and even more preferably 0.1 or more and 3 or less.
[0118] The content of the cationic resin in the base particle (the amount of the first layer coated on the entire base particle) is preferably 0.01% by mass or more and 20% by mass or less, more preferably 0.1% by mass or more and 10% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less.
[0119] By setting the content of the cationic resin relative to the base particles within the above range, the alkali metal atomic weight A on the resin particle surface is more likely to be reduced, and therefore the storage property in a solution containing water is more improved.
[0120] Furthermore, from the viewpoint of further improving storage stability in a solution containing water, the content of the hydrophobic compound relative to the base particle (the amount of coating by the second layer relative to the entire base particle) is preferably 0.05% by mass or more and 15% by mass or less, more preferably 0.1% by mass or more and 10% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less.
[0121] Here, the coating amounts of the cationic resin and the hydrophobic compound (i.e., the coating amounts of the first layer and the second layer) are measured as follows. The coating amount of the cationic resin is determined by the difference between the amount of the cationic resin treated and the amount of the cationic resin obtained by drying the supernatant after the treatment. Similarly, the coating amount of the hydrophobic compound is determined by the difference between the amount of the hydrophobic compound treated and the amount of the hydrophobic compound obtained by drying the supernatant after the treatment.
[0122] <Characteristics of resin particles> (particle size) The volume average particle size of the biodegradable resin particles is preferably 3 μm or more and 100 μm or less, more preferably 5 μm or more and 70 μm or less, and even more preferably 8 μm or more and 60 μm or less. If the particle size of the granules is 3 μm or more, the number of particles per unit weight is not too large, so that the decrease in the biodegradation rate is suppressed. On the other hand, if the particle size of the biodegradable resin particles is 100 μm or less, the specific surface area is increased, and the biodegradation rate is further improved. Therefore, the volume average particle size of the granules is preferably within the above range.
[0123] The large diameter particle size distribution index GSDv of the biodegradable resin particles is preferably 1.5 or less, more preferably 1.3 or less, and even more preferably 1.2 or less. When the particle size distribution of the biodegradable resin particles is made closer to uniform, regular hydrolysis proceeds by providing a constant opportunity for contact with water, and the biodegradation rate is further improved.
[0124] The volume average particle size and the large particle size distribution index GSDp of the biodegradable resin particles are measured as follows. The particle size is measured using an LS particle size distribution analyzer "Beckman Coulter LS13 320 (manufactured by Beckman Coulter)" and the cumulative particle size distribution is plotted from the smallest diameter side on a volume basis. The particle size at 50% of the cumulative distribution is determined as the volume average particle size. On the other hand, the cumulative particle size distribution is plotted from the small diameter side on a volume basis, and the particle size at 50% of the cumulative distribution is defined as the number average particle size D50v, and the particle size at 84% of the cumulative distribution is defined as the number particle size D84v. The large diameter side number particle size distribution index GSDv is calculated by the formula GSDv=(D84v / D50v). 1 / 2 It is calculated as follows.
[0125] (Atomic weight A and atomic weight B) The amount of alkali metal atoms A present on the resin particle surface relative to the total amount of atoms present on the resin particle surface, as measured by X-ray photoelectron spectroscopy, and the amount of alkali metal atoms B present on the resin particle relative to the total amount of atoms present on the resin particle, as measured by X-ray fluorescence spectroscopy, satisfy the relationship of 0≦(A / B)<0.15 and 0.005 atomic%≦B≦0.5 atomic%.
[0126] From the viewpoint of further improving the storage stability in a solution containing water, the atomic weight A and the atomic weight B preferably satisfy 0≦(A / B)≦0.12, more preferably satisfy 0≦(A / B)≦0.10, and further preferably satisfy 0≦(A / B)≦0.07. From the viewpoint of improving biodegradability, the atomic weight B preferably satisfies 0.05 atomic %≦B≦0.40 atomic %, more preferably satisfies 0.10 atomic %≦B≦0.35 atomic %, and further preferably satisfies 0.15 atomic %≦B≦0.30 atomic %.
[0127] The alkali metal preferably contains Na. Here, the atomic weight A of Na present on the resin particle surface relative to the total atomic weight present on the resin particle surface is Na and the atomic weight B of Na present in the resin particles relative to the total atomic weight present in the resin particles, measured by X-ray fluorescence spectroscopy. Na However, 0≦(A Na / B Na )<0.15 and 0.005 atomic%≦B Na It is preferable that the relationship be ≦0.5 atomic %. Among alkali metals, Na tends to have a high effect of improving the biodegradability of biodegradable resins. Therefore, by including Na in the alkali metal, the biodegradability of the resin particles is further improved. And, the atomic weight A Na and atomic weight B Na When the above relationship is satisfied, the proportion of Na in the alkali metal contained in the resin particles becomes high, and the biodegradability of the resin particles is further improved.
[0128] The atomic weight A is calculated as follows. The X-ray photoelectron spectrometer used was an ULVAC-PHI PHI5000 Versa Probe II, and the measurement was performed using monochromated AlKα radiation as the X-ray source and an acceleration voltage of 15 kV. The sample tilt angle was adjusted to set the incidence angle θ at 15° to measure only the outermost surface of the particle, and the number of each atom was calculated based on the spectrum of each measured atom, and the alkali metal atomic weight relative to the total atomic weight in the measurement area was calculated. The alkali metal atomic weight A (atomic%) is the percentage of the total amount of detected alkali metal atoms relative to the total atomic weight detected.
[0129] The atomic weight B is calculated as follows. Qualitative and quantitative analysis measurements are performed using a fluorescent X-ray analyzer (Shimadzu Corporation, XRF1500) under the conditions of X-ray output 40V, 70mA, measurement area 10mmφ, and measurement time 15 minutes. Here, the elements to be analyzed are all elements in the measurement area, and based on the spectrum of each measured atom, the atomic weight of each element is calculated with reference to separately prepared calibration curve data that allows each element to be quantified, and the alkali metal atomic weight relative to the total atomic weight in the measurement area is calculated. The alkali metal atomic weight B (atomic%) is the percentage of the total amount of detected alkali metal atoms relative to the total atomic weight detected.
[0130] (Relationship between [AL1], [AL2] and [AL3]) [AL1], [AL2] and [AL3] are defined as follows: · [AL1]: The amount of alkali metal atoms on the surface of the resin particle measured by X-ray photoelectron spectroscopy. [AL2]: The amount of alkali metal atoms on the surface of a resin particle after etching a 2 mm square area of the surface with an argon gas cluster ion gun at 5 kV for 5 minutes. [AL3]: The amount of alkali metal atoms on the surface of a resin particle after etching a 2 mm square area of the surface with an argon gas cluster ion gun at 5 kV for 30 minutes. The resin particles according to this embodiment satisfy the relationship: [AL1]<[AL3]<[AL2].
[0131] In order to obtain resin particles that have better biodegradability and better storage stability in a solution containing water, it is preferable that [AL1], [AL2] and [AL3] are as follows. [AL1] is preferably 0 atomic % or more and 0.08 atomic % or less, more preferably 0 atomic % or more and 0.06 atomic % or less, and further preferably 0 atomic % or more and 0.03 atomic % or less. [AL2] is preferably 0.1 atomic % or more and 10 atomic % or less, more preferably 0.2 atomic % or more and 9 atomic % or less, and further preferably 0.3 atomic % or more and 8 atomic % or less. [AL3] is preferably 0.09 atomic % or more and 4 atomic % or less, more preferably 0.09 atomic % or more and 3 atomic % or less, and further preferably 0.09 atomic % or more and 2 atomic % or less.
[0132] In order to obtain resin particles that have better biodegradability and better storage stability in a solution containing water, it is preferable that [AL1], [AL2] and [AL3] further satisfy the following relationship. The absolute value of the difference between [AL1] and [AL3] (|[AL1]-[AL3]|) is preferably 0.01 or more and 4 or less, more preferably 0.01 or more and 3 or less, and even more preferably 0.01 or more and 2 or less. The absolute value of the difference between [AL3] and [AL2] (|[AL3]-[AL2]|) is preferably 0.01 or more and 9.91 or less, more preferably 0.01 or more and 8.91 or less, and even more preferably 0.01 or more and 7.91 or less.
[0133] The alkali metal atomic weight is measured by XPS (X-ray photoelectron spectroscopy). The procedure for measuring the alkali metal atomic weights [AL1], [AL2] and [AL3] is the same as for atomic weight A. Specifically, [AL1] is measured using the same procedure as for atomic weight A (i.e., [AL1] is the same as atomic weight A). Then, a 2 mm square area on the surface of the resin particle is etched for 5 minutes with an argon gas cluster ion gun at an output of 5 kV, and the alkali metal atomic weight [AL2] is measured on the surface under the same XPS measurement conditions as for atomic weight A. Furthermore, a 2 mm square area on the surface of the resin particle is etched for 30 minutes with an argon gas cluster ion gun at an output of 5 kV, and the alkali metal atomic weight [AL3] is measured on the surface under the same XPS measurement conditions as for atomic weight A.
[0134] A method for etching the surfaces of the resin particles will also be described. Specifically, a 2 mm square area of the outermost surface of a resin particle is etched with an argon gas cluster ion gun with an output of 5 kV. -Etching conditions- Etching gun: Argon gas cluster ion gun Acceleration voltage: 5 kV Sweep area: 2mm x 2mm Rate: 20 nm / min (polyester equivalent)
[0135] <Method of manufacturing resin particles> The resin particles can be produced, for example, by the following method. (1) A kneading and grinding method in which the components are kneaded together, and the resulting kneaded mixture is ground and classified to obtain granules; (2) A dry manufacturing method in which the shape of granules obtained by the kneading and grinding method is changed by mechanical impact force or thermal energy to obtain granules. (3) A method in which particle dispersions of each component are mixed, the particles in the dispersion are agglomerated, and then heat-fused to obtain granules. (4) A dissolution suspension method in which the organic solvent in which each component is dissolved is suspended in an aqueous solvent to produce granules containing each component. (5) A kneading and dissolving method in which each component and a binder are kneaded and extruded to form pellets, and the resulting pellets are stirred in a solvent that dissolves only the binder to form granules.
[0136] The method for producing resin particles is such that atomic weight A and atomic weight B satisfy the relationship of 0≦(A / B)<0.15 and 0.005 atomic %≦B≦0.5 atomic %, and is as follows: It is preferable to produce it by the above method (4).
[0137] In the production of resin particles by the above method (4), it is preferable to have a step (hereinafter also referred to as step A) of suspending the organic solvent in which each component is dissolved in an aqueous solvent, adding an alkali metal element source to the suspension, stirring for example at a temperature range of 60°C or higher and 90°C or lower for example for 2 hours or higher and 5 hours or lower, and then removing the solvent to obtain coarse particles. After step A, it is preferable to have a step of adding a dilute acid to the coarse particles and then filtering the mixture (hereinafter, also referred to as step B). Furthermore, after step B, it is preferable to have a step (hereinafter also referred to as step C) of dispersing the coarse particles obtained in step B in water and filtering the dispersion.
[0138] -Process A- The source of the alkali metal element to be added to the suspension is preferably a hydroxide containing an alkali metal element. Specific examples of hydroxides containing an alkali metal element include lithium hydroxide, sodium hydroxide, potassium hydroxide, and rubidium hydroxide. The amount of the alkali metal element source added is preferably from 2 to 20% by mass, and more preferably from 3 to 10% by mass, based on the total solid content contained in the suspension. Here, the method for adding the alkali metal element source to the suspension is preferably a method in which an aqueous solution containing the alkali metal element source is added to the suspension.
[0139] -Process B- Dilute hydrochloric acid is preferred as the dilute acid added to the coarse particles obtained in step A. The concentration of hydrogen chloride relative to the total dilute hydrochloric acid is preferably 9% by mass or more and 11% by mass or less. The amount of dilute acid added is preferably 100 parts by mass or more and 3000 parts by mass or less, more preferably 200 parts by mass or more and 1000 parts by mass or less, and even more preferably 400 parts by mass or more and 800 parts by mass or less, relative to 100 parts by mass of the coarse particles obtained in step A.
[0140] In the step B, the method for filtering the dispersion liquid containing the coarse particles and the dilute acid is not particularly limited, and a known filtering method can be applied. The same applies to the filtering method applied in the step C.
[0141] -Process C- The amount of water in which the coarse particles obtained in step B are dispersed is preferably 100 parts by mass or more and 3,000 parts by mass or less, more preferably 200 parts by mass or more and 1,000 parts by mass or less, and even more preferably 400 parts by mass or more and 800 parts by mass or less, relative to 100 parts by mass of the coarse particles obtained in step B.
[0142] In step C, it is also preferable to repeat a series of steps consisting of dispersing the coarse particles obtained in step B in water and filtering the dispersion liquid multiple times under the same conditions. When the series of steps is repeated multiple times, the number of times is preferably 2 to 4.
[0143] After step C, the residue after filtration is dried to obtain resin particles.
[0144] The resin particles having the first layer and the second layer can be produced, for example, by the following method.
[0145] -First step- In the first step, base particles are prepared. The base particles can be produced by the above-mentioned resin particle production methods (1) to (5).
[0146] Next, an aqueous dispersion is prepared in which the obtained base particles are dispersed. Prior to preparing the aqueous dispersion, it is preferable to wash the base particles with an acid.
[0147] Next, the aqueous dispersion, the aqueous dispersion in which the base particles are dispersed, and an aqueous solution containing a cationic resin are mixed together, whereby, for example, the hydroxyl groups of the resin contained in the base particles react with the amine sites of the cationic resin to form a first layer.
[0148] -Second process- In the second step, the base particles on which the first layer is formed are taken out from the mixed liquid. The base particles are taken out, for example, by filtering the mixed liquid. The taken out base particles are preferably washed with water. This makes it possible to remove unreacted cationic resin.
[0149] Next, after preparing an aqueous dispersion in which the base particles are dispersed, the aqueous dispersion is mixed with an emulsion solution of an anionic or nonionic hydrophobic compound, so that the emulsion of the hydrophobic compound is adsorbed onto the first layer of the base particles. The mixture is then dried, breaking up the emulsion of the hydrophobic compound and coating the hydrophobic compound on the first layer, thereby forming a second layer.
[0150] Through the above steps, the resin particles according to the present embodiment are obtained.
[0151] <Application> Applications of the resin particles according to this embodiment include granular materials such as cosmetic base materials, rolling agents, abrasives, scrubbing agents, display spacers, materials for forming beads, light diffusing particles, resin reinforcing agents, refractive index control agents, biodegradation accelerators, fertilizers, water absorbing particles, toner particles, and anti-blocking particles. EXAMPLES
[0152] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0153] <Preparing each ingredient> The following materials were prepared:
[0154] [Biodegradable resin] CAB1: Eastman Chemical "CAB381-20", cellulose acetate butyrate, weight average degree of polymerization 890, acetyl group substitution degree 1.05, butyryl group substitution degree 1.74. CAB2: Eastman Chemical "CAB171-15", cellulose acetate butyrate, weight average degree of polymerization 754, acetyl substitution degree 2.07, butyryl substitution degree 0.73 ·CAP: Eastman Chemical "CAP482-20", cellulose acetate propionate weight average degree of polymerization 716, acetyl group substitution degree 0.18, propionyl group substitution degree 2.49. ·PA12: Daicel Evonik "DAIAMID", Polyamide 12 PA11: Arkema "Rilsan", Polyamide 11 PBS: Mitsubishi Chemical Corporation's "BioPBS", polybutylene succinate DAC: Daicel Corporation "L-50", cellulose diacetate, weight average degree of polymerization 570
[0155] [Plasticizer] DBA: Kao "Vinicizer 40", diisobutyl adipate CDN: Cardolite "NX-2026", cardanol, molecular weight = 298-305 ATBC: "Citroflex A4" manufactured by Morimura Shoji Co., Ltd., acetyl tributyl citrate DPS: Nikko Chemicals "NIKKOL DIS", isopropyl sebacate
[0156] [First layer cationic resin] The number average molecular weight of each cationic resin is shown in the table. PEI1: Polyethyleneimine PEI2: Polyethyleneimine PEI3: Polyethyleneimine PAA: "PAA-25" manufactured by Nittobo Medical Co., Ltd., polyallylamine PBAM: Mitsubishi Chemical Corporation "PVAM-0595B", polyvinylamine
[0157] [Anionic or cationic hydrophobic compound of the second layer] EMUSTAR-0413: Carbana wax made by Nippon Seiro Co., Ltd. POLON-MN-ST: Dimethyl silicone manufactured by Shin-Etsu Chemical Co., Ltd. · KM-9717: MQ resin manufactured by Shin-Etsu Chemical Co., Ltd. BELSIL DM3112VP: Dimethicone manufactured by Asahi Kasei Wacker Silicone Co., Ltd. - Hi-Tech E-2213: Polyethylene wax manufactured by Toho Chemical Industry Co., Ltd. -Hi-Tech P-9018: Polypropylene wax manufactured by Toho Chemical Industry Co., Ltd. 3MF-320: Acrylic resin manufactured by Taisei Fine Chemical Co., Ltd. A-647GEX: Polyester resin manufactured by Takamatsu Oil Co., Ltd. WBR-016U: Urethane resin manufactured by Taisei Fine Chemical Co., Ltd.
[0158] [Examples 1 to 11, 15 to 33, 34 to 36, 38 to 41, Comparative Examples 1, 2, 6 to 8] (Preparation of mother particles) A total of 200 g of the biodegradable resin and plasticizer shown in Table 1 were completely dissolved in 800 g of methyl ethyl ketone in the composition ratio shown in Table 1. This was added to an aqueous solution in which calcium carbonate in the amount shown in Table 1, 2 g of carboxymethyl cellulose, and 200 g of methyl ethyl ketone were dispersed in 600 g of distilled water, and the solution was stirred for 5 minutes at 8000 rpm in a high-speed emulsifier (manufactured by IKA). 200 g of 1 mol / L sodium hydroxide was added to the solution, which was heated to 80°C and stirred for 3 hours to remove the methyl ethyl ketone. Next, 10% dilute hydrochloric acid in the amount shown in Table 1 was added to dissolve the calcium carbonate, and then filtration was carried out to recover the solid content. The collected solid content was dispersed in the amount of pure water shown in Table 1, and then filtered. This series of steps was repeated the number of times shown in Table 1 to obtain a base particle slurry.
[0159] (Preparation of resin particles) 500 parts of the base particle slurry was prepared so that the solid content was adjusted to 20%. The cationic resin solution was added to the solid content (100 parts) contained in this slurry in the amount shown in Table 1 in terms of pure content, and stirred for 1 hour under conditions of 25 ° C. After stirring, the residue was filtered and dispersed again in pure water to prepare 500 parts of the slurry so that the solid content was adjusted to 20%. The hydrophobic compound was added to the solid content (100 parts) contained in this slurry in the amount shown in Table 1 in terms of pure content, and stirred for 1 hour under conditions of 25 ° C. After stirring, the residue was filtered, and the solid content was freeze-dried to obtain biodegradable resin particles. Through the above steps, biodegradable resin particles were obtained.
[0160] [Example 12] Resin particles were obtained in the same manner as in Example 1, except that 200 g of 1 mol / L sodium hydroxide was added during the preparation of the base particles, but 120 g of 1 mol / L lithium hydroxide was added.
[0161] [Example 13] Resin particles were obtained in the same manner as in Example 1, except that 200 g of 1 mol / L sodium hydroxide was added during the preparation of the base particles, but 280 g of 1 mol / L potassium hydroxide was added.
[0162] [Example 14] A base particle slurry was obtained in the same manner as in Example 1, except that 200 g of 1 mol / L sodium hydroxide was added during preparation of the base particles, but 515 g of 1 mol / L rubidium hydroxide was added.
[0163] [Example 37, Comparative Examples 3 to 5] (Preparation of resin particles) A total of 200 g of the biodegradable resin and plasticizer shown in Table 1 were completely dissolved in 800 g of methyl ethyl ketone in the composition ratio shown in Table 1. This was added to an aqueous solution in which calcium carbonate in the amount shown in Table 1, 2 g of carboxymethyl cellulose, and 200 g of methyl ethyl ketone were dispersed in 600 g of distilled water, and the solution was stirred for 5 minutes at 8000 rpm in a high-speed emulsifier (manufactured by IKA). 200 g of 1 mol / L sodium hydroxide was added to the solution, which was heated to 80°C and stirred for 3 hours to remove the methyl ethyl ketone. Next, 10% dilute hydrochloric acid in the amount shown in Table 1 was added to dissolve the calcium carbonate, and then filtration was carried out to recover the solid content. The collected solids were dispersed in the amount of pure water shown in Table 1, and a series of steps including filtration was repeated the number of times shown in Table 1. The solids were then freeze-dried to obtain resin particles.
[0164] <Evaluation> (Atomic weight and particle size measurement) The atomic weight A, atomic weight B, [AL1], [AL2], [AL3], and number average particle diameter D50v of the obtained resin particles were measured according to the described methods.
[0165] (Storage evaluation: Measurement of mass loss rate in distilled water) 5 g of the obtained resin particles were sealed in a bag made of a nylon net with an opening of 1 μm (manufactured by AS ONE, nylon mesh #508 / 585-1 μm), placed in pure water at 70°C, and left for 14 days. The mass of the nylon net containing the resin particles before and after leaving it was measured, the mass loss rate was calculated, and the storage stability was evaluated based on the following evaluation criteria. A(◎): Mass loss is less than 5% B(〇): Mass loss is 5% or more but less than 10% C(△): Mass loss is 10% or more but less than 30% D(×): Mass reduction amount is 30% or more
[0166] (Biodegradability evaluation: Measurement of mass loss rate in compost) Five grams of the obtained resin particles were sealed in a bag made of processed nylon netting with 1 μm mesh (manufactured by AS ONE, nylon mesh #508 / 585-1 μm), and the bag was buried in compost (manufactured by Iris Ohyama, compost bed) containing a total nitrogen content of 1% to less than 3% by mass, a total phosphoric acid content of 0.1% to less than 1% by mass, and a total base content of 2% to less than 4% by mass, and having a carbon-nitrogen ratio (C / N ratio) of 20 to less than 30.Then, the bag was left in a dry oven set at 55°C for 14 days, and the mass of the nylon netting containing the resin particles was measured before and after leaving the bag, the mass loss rate was calculated, and storage stability was evaluated based on the following evaluation criteria. A(◎): Mass reduction of 95% or more B(〇): Mass loss is 90% or more but less than 95% C(△): Mass loss is more than 70% but less than 90% D(×): Mass reduction amount is 70% or less
[0167] [Table 1-1]
[0168] [Table 1-2]
[0169] [Table 2-1]
[0170] [Table 2-2]
[0171] From the above results, it is apparent that the resin particles of this example are biodegradable and have excellent storage properties in a solution containing water.
Claims
1. A method for producing a polymeric material comprising the steps of: (a) providing a polymeric material having a base particle containing at least one biodegradable resin selected from the group consisting of cellulose acylate and aliphatic polyester; an amount A of alkali metal atoms present on the resin particle surface relative to the total amount of atoms present on the resin particle surface, as measured by X-ray photoelectron spectroscopy, and an amount B of alkali metal atoms present on the resin particle relative to the total amount of atoms present on the resin particle, as measured by X-ray fluorescence spectroscopy, satisfy the relationships 0≦(A / B)<0.15 and 0.005 atomic%≦B≦0.5 atomic%, The resin particles have a volume average particle size of 3 μm or more and 100 μm or less.
2. 2. The resin particles according to claim 1, wherein the alkali metal comprises Na.
3. Resin particles described in claim 1 or claim 2, wherein the content of the cellulose acylate is 50 mass% or more relative to the entire mother particle.
4. 4. The resin particles according to claim 3, wherein the cellulose acylate has at least two kinds of acyl groups.
5. 5. The resin particles according to claim 4, wherein the cellulose acylate having at least two kinds of acyl groups is cellulose acetate butyrate.
6. a first layer on the surface of the base particle, the first layer including at least one cationic resin selected from the group consisting of polyalkyleneimine, polyallylamine, and polyvinylamine; A first layer containing an anionic or nonionic hydrophobic compound, and a second layer containing an anionic or nonionic hydrophobic compound, in this order.
7. 7. The resin particle according to claim 6, wherein the amount of the coating with the first layer is 0.01% by mass or more and 20% by mass or less based on the entirety of the base particle.
8. A method for producing a polymeric material comprising the steps of: (a) providing a polymeric material having a base particle containing at least one biodegradable resin selected from the group consisting of cellulose acylate and aliphatic polyester; the amount of alkali metal atoms measured by X-ray photoelectron spectroscopy, wherein the amount of alkali metal atoms [AL1] on the surface of the resin particle, the amount of alkali metal atoms [AL2] on the surface after etching a 2 mm square area of the surface of the resin particle with an argon gas cluster ion gun having an output of 5 kV for 5 minutes, and the amount of alkali metal atoms [AL3] on the surface after etching a 2 mm square area of the surface of the resin particle with an argon gas cluster ion gun having an output of 5 kV for 30 minutes satisfy the relationship [AL1] < [AL3] < [AL2], The resin particles have a volume average particle size of 3 μm or more and 100 μm or less.
Citation Information
Patent Citations
Masterrslave type servoomanipulator
JP1981033291A
Capacitor motor
JP1983029393A
Cellulose derivative particle, its manufacturing method and cosmetic using the same
JP2003252903A
Polyester resin composition, production method therefor, and molding
JP2009249577A
Cellulose particulate aggregate
JP2013173861A